2018
DOI: 10.1039/c8cc02430h
|View full text |Cite
|
Sign up to set email alerts
|

The role of mid-gap states in all-inorganic CsPbBr3 nanoparticle one photon up-conversion

Abstract: CsPbBr3 nanoparticles that have been treated with NH4SCN to produce essentially trap-free surfaces show an increase of one photon up-conversion quantum yield with little change to the up-conversion energy of activation, as estimated using an Arrhenius analysis. This suggests that mid-gap trap states constitute a loss pathway, and may not be integral to the one-photon excitation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 23 publications
6
45
0
Order By: Relevance
“…The converse process, in which a material emits higher energy light than it absorbs, is commonly known as luminescence up-conversion [1,2]. While the majority of research into luminescence up-conversion is focused on nonlinear, multi-photon excitation mechanisms, there are material systems for which one-photon up-conversion, also called anti-Stokes photoluminescence (ASPL), is possible [3][4][5][6][7][8][9][10][11]. As the name implies, ASPL is the reverse process of the thermalization loss that gives rise to Stokes-shifted PL.…”
Section: Introductionmentioning
confidence: 99%
“…The converse process, in which a material emits higher energy light than it absorbs, is commonly known as luminescence up-conversion [1,2]. While the majority of research into luminescence up-conversion is focused on nonlinear, multi-photon excitation mechanisms, there are material systems for which one-photon up-conversion, also called anti-Stokes photoluminescence (ASPL), is possible [3][4][5][6][7][8][9][10][11]. As the name implies, ASPL is the reverse process of the thermalization loss that gives rise to Stokes-shifted PL.…”
Section: Introductionmentioning
confidence: 99%
“…This entails observations of redshifted ASPL spectra relative to the normal NC/nanostructure band edge emission. These redshifts have been observed in CdS 1 − x Se x 110 , CdSe 59,62,109 , CdTe 59,63,65,66,71,105,112,113 , PbS NC-doped glasses 67,115 , CsPbBr 3 73,103 , and CsPbBrI 2 NCs 69 . Figure 9a provides an example, showing the apparent~8 meV redshift between the emission and ASPL spectra of a CsPbBr 3 NC ensemble.…”
mentioning
confidence: 74%
“…Lowering NC/nanostructure trap densities should therefore increase I ASPL . This last prediction is important because it has been observed that I ASPL increases with increasing QYs in both CdSe 60,61 and CsPbBr 3 NCs 73 . We also observe this behavior in CdSe/ CdS NCs studied here.…”
mentioning
confidence: 87%
See 2 more Smart Citations